UMOCOWANIE DO ZAWARCIA UMOWY O ARBITRAŻ - Pazdan, Jadwiga (Zeszyty Prawnicze, 2017)
Power to Conclude an Arbitration Agreement on Behalf of Another Person Summary The legal character of an arbitration agreement is disputable in the Polish doctrine. However, it is undisputable that such an agreement may be concluded by an agent. I mean here a power of attorney of the substantive law, and not the power to represent in the court proceedings. A principal may expressly authorize an agent to conclude a particular arbitration agreement (a specific power of attorney) or to conclude all arbitration agreements (a generic power of attorney). A question, however, arises, whether an agent authorized to enter into a specific civil or commercial law contract or contracts of specific kind who was not expressly authorized by a principal to conclude an arbitration agreement may conclude such agreement in relation to the disputes which may result from these contracts. This question should be answered positively. An agent who was given only a general authorization to act on behalf of the principal, cannot in principle conclude an arbitration agreement, unless the dispute concerns the sphere in which an agent has a power to act. This sphere is confined to acts within a regular management. One should look for a law applicable to the power of attorney to conclude an arbitration agreement according to the method accepted generally in private international law for authorization, and not according to the rule applied in relation to a power to represent in the court proceedings. The Polish 1965 Private International Law Act does not determine the law applicable to the authorization. This gap should be filled using the following solution: a) the choice of law made by a principal (or by a principal and an agent) is effective against the third party , if this party knew about the choice or could and ought to have known about it, b ) in case of the lack of choice, the law of the country in which an agent permanently conducts his professional activity related to the authorization should be applied (the law of agent’s seat), if the third party with whom an agent concluded an agreement knew the agent’s seat or could, with due diligence, identify it, c ) in case of the lack of choice and when an agent has no permanent seat, one should apply the law where an agent acts.